Technology, innovation and healthcare : an evolving relationship - Richards, Bernadette J.; Taylor, Mark; Jacobson, Susannah Sage (Elgar studies in health and the law, 2022)
"This timely book emphasizes the importance of regulation in enabling and channelling innovation at a time when technology is increasingly embedded in healthcare. It considers the adequacy of current regulatory approaches, identifying apparent gaps, risks and liabilities, and discusses how these might be collectively addressed. The authors present possible solutions that balance the protection and promotion of public trust in healthcare against enabling technological progress and disruptive innovation. Offering both a theoretical and practical approach to challenges at the intersection of healthcare, law and technology, this thought-provoking book explores broad questions of regulation and innovation before analysing contextual applications of these topics. It moves from a wide-ranging consideration of the polycentric and changing nature of health regulation through to a more specific examination of topics including patient consent, the role of device representatives, privacy, artificial intelligence and big data. Providing an international perspective, Technology, Innovation and Healthcare will be a valuable resource for scholars and students of health law, innovation, technology law, law and development and law and society. It will also be of benefit to lawyers, healthcare professionals, technology developers and policy makers, seeking to better integrate technology with healthcare"--